2020
DOI: 10.1155/2020/1357192
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Adequately Iodized Dietary Salt and Associated Factors in a Town of Southeast Ethiopia: A Community-Based Cross-Sectional Survey

Abstract: Background. Iodine deficiency is the world’s major cause of preventable intellectual impairment, and nearly 2 billion people are at risk of iodine deficiency worldwide. Prevention and control of iodine deficiency disorders primarily aim at ensuring the intake of adequate iodine to maintain normal thyroid function. In our study area, studies regarding the coverage of adequately iodized salt at household level are meager. Hence, this study aimed to assess the magnitude of adequately iodized dietary salt at a hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…The high percentage (97%) of use of iodized salt by the restaurants and bakeries may be due to the efforts of the Cape Verdean government to stimulate improvements in the iodine status in recent years. This rate is consistent with that found in a study conducted in Nigeria (95%) and is higher than that found in studies in Ghana (75.6%) and Senegal (10%) on the salt iodine content in the household diet and associated factors (16,17).…”
Section: Discussionsupporting
confidence: 91%
“…The high percentage (97%) of use of iodized salt by the restaurants and bakeries may be due to the efforts of the Cape Verdean government to stimulate improvements in the iodine status in recent years. This rate is consistent with that found in a study conducted in Nigeria (95%) and is higher than that found in studies in Ghana (75.6%) and Senegal (10%) on the salt iodine content in the household diet and associated factors (16,17).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, this finding is higher than the studies conducted in Wolaita (37.7%) [27], Dabat district (33.2%) (16), Gondar (28.9%) [28], Benishangul Gumuz (26.1%) [29], Laelay Maychew District (33%) [30], and zuway (30.7%) [31]. This discrepancy could be correlated to a change in the time when the studies were done [32]. As evidence from the Ethiopian demographic and health survey, the coverage of iodized salt increased from 28.4% in 2000 to 89% in 2016 [11].…”
Section: Discussionmentioning
confidence: 81%
“…Despite these and other efforts made by the Ethiopian government, several recent researches had shown conflicting results about the Ethiopia’s progress toward achieving the goal of USI. 3,11,51,53…”
Section: Resultsmentioning
confidence: 99%
“…3 Another study conducted in northeast Ethiopia had shown high prevalence of goiter (42.5%). 51 Similarly, the southeast Ethiopian study revealed only 56.6% of households were using adequately iodized salt 53 which is far below WHO recommendation (> 90%).…”
Section: Iodine Content Of Household Salt In the Last 2 Decades In Et...mentioning
confidence: 99%
See 1 more Smart Citation